Partitioning evapotranspiration by measuring soil water evaporation with heat-pulse sensors and plant transpiration with sap flow gauges - Wang, Yueyue; Horton, Robert; Xue, Xuzhang; Ren, Tusheng (Agricultural water management, 2021)
Understanding the contributions of soil water evaporation (E) and crop transpiration (T) to evapotranspiration (ET) is essential for irrigation management and improving crop water use efficiency. Current methods for partitioning ET are subject to uncertainties, due in part to the scale differences in determining E, T, and ET. In this study, ET of a lysimeter planted with maize (Zea mays L.) was partitioned into E and T using sensors that had compatible measurement scales: E was measured with heat pulse sensors (following the sensible heat balance (SHB) and modified sensible heat balance (MSHB) approaches), and T was measured with sap flow gauges (following the heat-balance sap-flow (HBSF) method). The accuracy of the measurements was evaluated by comparing the sum of E and T values (E + T) to weighing lysimeter ET data. During the study period, E, T, and ET had average values of 0.9, 4.0, and 4.8 mm d−1, respectively, and the fractions of E and T were 19% and 81% of E + T, respectively. In general, the E + T values agreed well with the lysimeter ET data, but slight overestimations and underestimations were observed at relatively small and relatively large ET rates, respectively. By combining the SHB and MSHB approaches and the HBSF method, it is possible to partition ET into E and T with satisfactory accuracy. •A combination approach is introduced to monitor E with heat pulse sensors and T with sap flow sensors.•E and T values accounted for about 19% and 81% of the total E + T during the measurement period.•Cumulative E + T of the combination approach agreed well with cumulative ET from a lysimeter.•E + T slightly underestimated ET at lower rates, and slightly overestimated ET at larger rates.